Pengendalian Kualitas pada Industri Manufaktur dengan menggunakan Statistical Process Chart - Imam Husni Al Amin; Endro Prihastono; Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2008)
Consument satisfied once gone to win manufacture on side profit course Once work manufacture as quality level or product quality. When quality product this goods. may afterwards layal consument side in producl and as payment to product. Sometime ansurace automatic survival imperishableness manufactured thought not manufacturing all to have quality control deparment but they conscious capable and to compete quality control product deparment on construction less looses payment and productifìty level, Manufactured which to exist deparment or quality control ãeparment 80% quantity and only whichjust 20% have not deparment quantity